2022
DOI: 10.1111/geb.13512
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological processes shape plant community traits in the Arctic

Abstract: Aim: Geomorphological processes profoundly affect plant establishment and distributions, but their influence on functional traits is insufficiently understood. Here, we unveil trait-geomorphology relationships in Arctic plant communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Former studies have shown the importance of snow persistence when examining taxonomic (Löffler and Pape 2008, Niittynen et al 2018) and functional (Niittynen et al 2020) vascular plant diversity. Likewise, fluvial conditions and other geomorphological features are known to be fundamental predictors of species richness (le Roux and Luoto 2013) and community functional composition in tundra (Kemppinen et al 2022). Our study corroborates these findings and highlights the importance of snow persistence and fluvial disturbance on phylogenetic diversity as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Former studies have shown the importance of snow persistence when examining taxonomic (Löffler and Pape 2008, Niittynen et al 2018) and functional (Niittynen et al 2020) vascular plant diversity. Likewise, fluvial conditions and other geomorphological features are known to be fundamental predictors of species richness (le Roux and Luoto 2013) and community functional composition in tundra (Kemppinen et al 2022). Our study corroborates these findings and highlights the importance of snow persistence and fluvial disturbance on phylogenetic diversity as well.…”
Section: Discussionmentioning
confidence: 99%
“…Fluvial processes create varying habitats, redistribute water and nutrients as well as generate disturbance for vegetation affecting both species richness and community composition (le Roux and Luoto 2013, Kemppinen et al 2022). Fluvial disturbance (Fluvial, Supporting information) was incorporated in our models by calculating distance to running waters using digitised stream network and digital elevation model at 2‐m resolution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is already evidence that increased instances of hot, dry days have increased soil erosion in Iceland (Owczarek et al, 2022). Higher variability in soil moisture will lead to increased moisture stress, compounded by reduced organic layer depths and reduced water retention capacity (Kemppinen et al, 2022). More frequent extreme weather—particularly rainstorms and periods of high winds—will increase erosive forces.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors combine to promote high‐latitude soil erosion, including vegetation type and cover, soil type, spatiotemporal patterns of snow lie, the magnitude and frequency of freeze–thaw cycles, degree of exposure to winds and grazing by large herbivores. Soil moisture is a critical but frequently overlooked factor, as it has been shown to impact plant growth and—by extension—the ability of vegetation cover to retard erosion (Berdanier & Klein, 2011; Kemppinen et al, 2022). Drought is obviously stressful to plants (Grace, 1997), but variability in soil moisture levels (e.g., rapid cycling between soaked and parched conditions) can also lead to reduced growth and sparser cover (Kemppinen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%